Fishermen's Perception of the Readiness of Safety Equipment in Supporting Navigation Safety on Tanakeke Island - Muhammad Saleh; Rukmini Rukmini; Heri Sutanto; Yudi Satria; Rusli Achmad (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Sailing safety is a crucial aspect of maritime activities, especially for fishermen who face a high risk of accidents at sea. The problems encountered in the Tanakeke Islands demonstrate the low level of attention to the availability of safety equipment on board vessels, which has resulted in a high number of accidents. Objective: This study aims to determine fishermen's perceptions of the availability of safety equipment and its impact on sailing safety. Methods: The research method used was descriptive qualitative, with data collected through observation, interviews, documentation, and questionnaires from 29 fishermen. Results: The study showed that most fishermen had a positive perception of the importance of safety equipment, with an average score of 79.34, although cultural beliefs persist that the provision of safety equipment is considered unconventional. The main factors contributing to accidents include extreme weather conditions and technical damage to vessels. Efforts to improve safety are being carried out through outreach, vessel repairs, and increased awareness among fishermen. Conclusion: The conclusion of this study indicates that the availability of safety equipment plays a crucial role in supporting sailing safety, but increased awareness and adequate facilities are still needed.